Synergistic Effects of Pursed-Lip Breathing and Music Therapy on Oxygen Saturation in Pulmonary Tuberculosis: A Narrative Literature Review - Carlos Borromeu de Assis Belo; Indah Sri Wahyuningsih; Dwi Heppy Rochmawati; Erna Melastuti (International Journal of Pharmaceutical and Bio Medical Science, 2026)
Background: Pulmonary tuberculosis remains a significant global health problem and is often associated with impaired gas exchange leading to decreased oxygen saturation. Non-pharmacological interventions such as pursed-lip breathing and music therapy have been explored to improve respiratory function and enhance patient comfort. Objective: This review aims to analyze the synergistic effects of pursed-lip breathing and music therapy on oxygen saturation in patients with pulmonary tuberculosis. Methods: A narrative literature review was conducted on articles published between 2021 and 2026. Literature searches were performed using databases including PubMed, Google Scholar, ScienceDirect, DOAJ, and Garuda with relevant keywords. A total of 15–20 articles were selected based on inclusion criteria and analyzed descriptively. Results: The findings indicate that pursed-lip breathing improves ventilation efficiency, prolongs exhalation, and enhances oxygen exchange, while music therapy promotes relaxation, reduces anxiety, and stabilizes respiratory patterns. Several studies reported improvements in oxygen saturation and overall respiratory parameters following these interventions. Discussion: The combination of pursed-lip breathing and music therapy may produce synergistic effects by integrating physiological and psychological mechanisms, leading to improved oxygenation and reduced respiratory distress in pulmonary tuberculosis patients. Conclusion: Pursed-lip breathing combined with music therapy shows potential as a complementary intervention to improve oxygen saturation in pulmonary tuberculosis, although further high-quality studies are needed to strengthen the evidence.